BBS10 mutations are common in 'Meckel'-type cystic kidneys. Issue 12 (30th August 2010) - Putoux, Audrey; Mougou-Zerelli, Soumaya; Thomas, Sophie; Elkhartoufi, Nadia; Audollent, Sophie; Le Merrer, Martine; Lachmeijer, Augusta; Sigaudy, Sabine; Buenerd, Annie; Fernandez, Carla; Delezoide, Anne-Lise; Gubler, Marie-Claire; et al.
Abstract : Background: Bardet–Biedl syndrome (BBS) is a genetically heterogeneous, multisystemic disorder characterised by progressive retinal dystrophy, obesity, hypogenitalism, learning difficulties, renal abnormalities and postaxial polydactyly, with only the last two antenatally observable. BBS is inherited as an autosomal recessive disorder, and 14 genes have been identified to date ( BBS1–BBS14 ). In addition, a complex digenic inheritance has been established in some families. Mutations of the BBS10 gene on chromosome 12q21.2 account for 20% of BBS cases. Methods: Given the fact that mutations in BBS genes have already been found in Meckel-like fetuses, and in light of the major contribution of BBS10 to BBS, the BBS10 gene was sequenced in 20 fetal cases and a child diagnosed antenatally presenting with characteristic renal anomalies and polydactyly, but without biliary dysgenesis. Results: Recessive mutations were identified at the BBS10 locus in five cases: four fetuses and a child. Interestingly, one of them had situs ambiguus, a rare feature in BBS. In the child, BBS gene screening identified a heterozygous BBS6 nonsense mutation in addition to the homozygous BBS10 mutation, in accordance with the suggested multigenic inheritance of the disease. Conclusions: These results confirm that BBS is underdiagnosed antenatally and should systematically be suspected in fetuses with severe cystic kidneys leading to oligoamnios and fetal or perinatal death. Moreover, this study confirms the high frequency of BBS10 mutations, particularly of the p.Cys91LeufsX5 allele, including severe lethal cases.